2246. Assessment of Factors Impacting Cervical Cancer Screening Rates Among Urban Women Living with HIV/AIDS. (26th November 2018) - Reynoso-Vasquez, Nicole; Kothari, Pooja; Haywood, Anna; Singh, Baljinder; Swaminathan, Shoba; DallaPiazza, Michelle
Abstract: Background: Although cervical cancer disproportionately affects women living with HIV, achieving high cervical cancer screening rates for this population continues to be a challenge. In our urban HIV clinic caring for 700 women, the baseline annual on-site screening rate was only 68% in 2017. The goal of this study was to identify factors related to low rates of screening in order to inform quality improvement efforts. Methods: Over the time period of January 1, 2015 and June 30, 2017, we conducted a retrospective chart review of 185 randomly selected women with HIV. We collected data on cervical cancer screening adherence according to the screening guidelines provided by the Department of Health and Human Services. Correlations between clinical and demographic factors and patterns of cervical cancer screening were analyzed using chi square and logistic regression. Results: During the review period, 68 (37%) patients completed two annual cervical cancer screenings, 96 (52%) completed 1, and 21 (11%) completed none. Of those completed, 22% were abnormal. When follow-up colposcopy was indicated, 18 of 42 (42%) women completed colposcopy within 6 months. Patients with screening rates lower than recommended were more likely to have substance use disorders and be uninsured ( P < 0.05). Factors significantly associated with adherence to screening guidelines included history of an abnormal pap test, current antiretroviral therapy, and more than four HIV-related primary care visits per year. Age and HIV viral load between the groups were not significantly different. Conclusion: In this urban HIV clinic cohort, a high proportion of women completed at least one cervical cancer screening test over a 2-year period, a promising result in the setting of a recent change in cervical cancer screening guidelines recommending less frequent testing. However, a smaller proportion completed colposcopy when indicated. The strongest predictors of low adherence to the guidelines were substance use disorder and lack of insurance. The next phase of this project will include a review of cervical and anal cancer screening rates among women, as well as patient surveys to determine quality improvement strategies that may further enhance acceptability and access to cervical and anal cancer screening and prevention. Disclosures: All authors: No reported disclosures.